THE EDUCATION AS A LIBERATING PRACTICE AND PILLAR OF THE HUMANIZATION PROCESS: TRANSDISCIPLINARY ESSAY FOR MORE EQUITABLE AND SUSTAINABLE SOCIETIES. (Isagoge - Journal of Humanities and Social Sciences, 2025)
This article addresses education as a condition for the ongoing process of humanization of the person, since, as a fruitful practice, it dignifies the individual and develops engaged citizens in an increasingly complex world. This work, therefore, is a reflective and critical essay on the problems of current education, especially at the higher education level, contrasting it with theoretical contributions to uncover the antinomies that permeate educational practices and the obstacles to a truly liberating education. The objective is to highlight the importance of the educational process as a means of raising awareness of the individual and their rights, but also of their duties in building more equitable societies, rooted in spatiality and environment, in ethical values, and in spirituality as a shared destiny. To this end, the reflection on educational praxis applies the dialectical and semiotic method to discover their meanings, assuming this cognitive path as a transdisciplinary search for the genuine sense of education. As a result, the degrading effects on the human condition are exposed when education is distorted, reduced to ideologies or masked as banal achievements. The paper concludes by establishing the depth of the quality education process, centered on effort, critical thinking, and constant improvement. This meta-knowledge is necessary to reverse these deviations and revalue education as the key to integral and equitable human development.
Keywords: Education; Liberating practice; Humanization; Human values; Awareness